Valorisation of Sea Bream By-Products Through Its Inclusion in Fish and Shrimp Burgers - Sara Pinar-Escobar; María Isabel Martínez; Ana Fuentes; José Manuel Barat-Baviera; Isabel Fernández-Segovia (Biology and Life Sciences Forum)
The aim of this work was to introduce the by-products generated by the sea bream processing industry as a new ingredient in the production of fish and seafood burgers. Fish by-product flour was obtained and added in the preparation of sea bream and shrimp burgers. The formulations selected from a sensory evaluation with semi-trained assessors were burgers with sea bream and shrimp (C) and the same sample with 10% of by-product flour (BP10). These formulations were subjected to sensory evaluation with consumers using hedonic scales. Both samples had a good acceptability, although the presence of by-products had a negative impact on the colour, resulting in a slight decrease in the global acceptance. It would be interesting to use a natural ingredient that could improve the colour of the product or use the by-product flour in battered products where the colour could be masked.